Der Gebrauch der Hl. Schrift in der dogmatischen Theologie - Becker, Karl Josef (Gregorianum, 1992)
The role of Scripture in dogmatic theology has to be understood from revelation and its characteristics. For revelation is primarily a personal encounter between God and man, in which through a man and in a human manner God reveals himself to men, awaits their response, which he himself supports. Revelation preserves this characteristic also in its transmission in the Church through Scripture, tradition, and magisterium. Scripture is transmission of revelation within the tradition to a specific, living generation of the Church. For only with the help of tradition does the Bible become a book written by the Spirit for this generation, a book that is legible in the Spirit. Therefore for its use in dogmatic theology Scripture cannot be treated as a merely human book nor as one to be studied with only human means. It is an historical and inspired book of which only a historical faithful reading using all human methods available within the context of tradition, can release the Christian meaning.